Pembentukan Karakter Islami di Desa Bolaromang - Khaerul Aqbar; Sirajuddin Sirajuddin; Aswar Aswar (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2023)
The Community Service Program (KKN) V for STIBA Makassar students aims to increase Islamic knowledge and religious skills in the people of Bolaromang Village, Buttono Pao District, Gowa Regency. Implementation of activities begins with mapping problems and needs using SOAR analysis. After analyzing the problems and needs, work programs are then prepared according to the needs of the community as a form of community service (PkM). The stages of PkM activities include: the observation stage, the preparation stage, the implementation stage, the mentoring stage, and the evaluation stage. Some of the programs/activities that have been successfully implemented are: Al-Qur'an Illiteracy Eradication, Religious Development, and the Saleh Children's Festival. From these activities, enthusiasm and support from elements of the village government, the taklim assembly, and the community were seen in quite large activities. The community feels the benefits after participating in this KKN program, including an increase in knowledge, insight and religious skills. The sustainability of this program is in the form of further coaching for the community, especially for fathers and youth.